1998
DOI: 10.1074/jbc.273.50.33741
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the cis-Acting Endoplasmic Reticulum Stress Response Element Responsible for Transcriptional Induction of Mammalian Glucose-regulated Proteins

Abstract: When unfolded proteins accumulate in the endoplasmic reticulum (ER), transcription of glucose-regulated proteins (GRPs) representing ER-resident molecular chaperones is markedly induced via the unfolded protein response (UPR) pathway. In contrast to recent progress in the analysis of yeast UPR, both cis-acting elements and transactivators responsible for mammalian UPR have remained obscure. Here, we analyzed the promoter regions of human GRP78, GRP94, and calreticulin genes and identified a novel element desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
992
2
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,132 publications
(1,042 citation statements)
references
References 55 publications
40
992
2
8
Order By: Relevance
“…36,42 These sequences are highly homologous with other ERSEs identified in the promoters of the BiP, GRP94, PDI and calreticulin (CRT) genes. 8,43 CHOP AARE was identified to be an essential motif for amino-acid activation of the CHOP promoter. 44 This sequence has weak homology with C/EBP-and ATF-binding sites.…”
Section: Transcriptional Regulation Of Chopmentioning
confidence: 99%
See 1 more Smart Citation
“…36,42 These sequences are highly homologous with other ERSEs identified in the promoters of the BiP, GRP94, PDI and calreticulin (CRT) genes. 8,43 CHOP AARE was identified to be an essential motif for amino-acid activation of the CHOP promoter. 44 This sequence has weak homology with C/EBP-and ATF-binding sites.…”
Section: Transcriptional Regulation Of Chopmentioning
confidence: 99%
“…6 The second response is upregulation of genes encoding ER chaperone proteins such as BiP/GRP78 and GRP94, enzymes including protein disulfide isomerase (PDI) and peptidyl-prolyl isomerase, and structural components of the ER including sarcoplasmic ER Ca 2 þ -ATPase 2 (SERCA2), to increase the protein-folding capacity in ER. [7][8][9] In addition to these genes, recent studies revealed that genes involved in translational recovery, amino-acid import, glutathione biosynthesis and protection against oxidative stress are also upregulated. 10 In a later phase, components of ER-associated degradation (ERAD), including ER degradation-enhancing a-mannosidase-like protein (EDEM), are transcriptionally induced to eliminate misfolded proteins in the ER by the ubiquitin-proteasome system.…”
mentioning
confidence: 99%
“…Luciferase reporters driven by the wild-type endoplasmic reticulum stress-response element (ERSEwt-Luc), a mutant ERSE (ERSEmut-Luc, a negative control), and the ERSE-II element (ERSEII3x-Luc) in the pGL3 vector were generously provided by Dr Kazutoshi Mori (HSP Research Institute, Kyoto Research Park, Kyoto, Japan) (Yoshida et al, 1998;Yamamoto et al, 2004). A CHOP (C/EBP homologous protein) promoter-luciferase reporter in the pGL3 vector (CHOP-Luc) was provided by Dr Pierre Fafournoux (Unite de Nutrition et Metabolisme Proteique, INRA de Theix, Saint Genes Champanelle, France) (Bruhat et al, 2000).…”
Section: Expression Vectors and Reporter Plasmidsmentioning
confidence: 99%
“…Disturbing this process by gene knock down might trigger ER stress and thus induce the UPR. One of the proteins known to be upregulated by the UPR is the ER chaperone calreticulin (Yoshida et al, 1998). To check if the ER stress system is activated by the knock down of LsKDELR and LsCOPB2, the mRNA expression levels of the salmon louse homologue of calreticulin (LsCalr) were assessed by qRT-PCR (Fig.…”
Section: Downstream Effects Of Knock Down Of Lskdelr and Lscopb2mentioning
confidence: 99%